2019
DOI: 10.1111/inm.12680
|View full text |Cite
|
Sign up to set email alerts
|

Improving physical health outcomes for people with severe mental illness: A proof‐of‐concept study of nurse practitioner candidate practice

Abstract: People with severe mental illness have significantly reduced life expectancy and higher risk of cardiovascular diseases than the general population. There is a critical need for quality physical health care to improve consumers’ health outcomes. There is minimal knowledge, however, on the impact of mental health nurse practitioner candidate (NPC) practices on consumers’ health outcomes. The aim of this proof‐of‐concept study was to describe the impacts of NPC practices on the quality of physical healthcare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Positive experiences with healthcare professionals could be attributed to their effective interpersonal skills when working with consumers, their useful and personalized health promotion advice and supportive approach (Edmunds 2018; Furness et al . 2020; Matthews et al . 2021; Watkins et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive experiences with healthcare professionals could be attributed to their effective interpersonal skills when working with consumers, their useful and personalized health promotion advice and supportive approach (Edmunds 2018; Furness et al . 2020; Matthews et al . 2021; Watkins et al .…”
Section: Resultsmentioning
confidence: 99%
“…Physical health interventions delivered by mental health nurses have been reported by consumers as positive, helpful, and valuable (Furness et al . 2020; Hassan et al . 2020a, 2020b; Rönngren et al .…”
Section: Resultsmentioning
confidence: 99%
“…2018; Furness et al . 2020). These studies have shown positive results in both increasing rates of CMM and providing clinical leadership within the settings, making CMM more visible to other staff (Brown et al .…”
Section: Discussionmentioning
confidence: 99%
“…2018) and community (Furness et al . 2020) teams, particularly with specialist roles such as physical health nurses and nurse practitioners to lead and strengthen physical health care. In addition to specialist physical healthcare roles in mental health settings, the findings of this study indicate a clear need to support consumers to attend specialist medical treatment for their physical health conditions.…”
Section: Relevance For Clinical Practicementioning
confidence: 99%
“…body mass index ≥30 kg/m 2 ) among consumers has been reported between 41% (Furness et al . 2020) to 59% (Annamalai et al . 2017) compared with the global population prevalence of 13% (World Health Organisation 2018c).…”
Section: Introductionmentioning
confidence: 99%